1998
DOI: 10.1080/10473289.1998.10463738
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Parameterization of Some Air Pollutants as a Function of Meteorological Parameters in Kayseri, Turkey

Abstract: In this paper, the statistical relations between meteorological parameters and some pollutant ground level concentrations are presented. The daily average sulfur dioxide and smoke values were measured at five stations in Kayseri over 20 months. The model adopted for analysis differed from the power-law form selected by former investigators. Wind speed, degree-day temperature, the percentage of relative humidity, the previous day's pollution concentrations, and the amount of global solar radiation were the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…The lower interquartile range (28 µg/m 3 ) was observed in the warm period and the higher range (43 µg/m 3 ) in the cold period of the year. The respective value of the transient period was found to be 32 µg/m 3 . This is probably due to the difference in deposition of pollutants as well as in emissions of pollutants between warm periods and the other periods of the year.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The lower interquartile range (28 µg/m 3 ) was observed in the warm period and the higher range (43 µg/m 3 ) in the cold period of the year. The respective value of the transient period was found to be 32 µg/m 3 . This is probably due to the difference in deposition of pollutants as well as in emissions of pollutants between warm periods and the other periods of the year.…”
Section: Resultsmentioning
confidence: 93%
“…The air pollution problem in many such areas, both densely populated and heavily industrialized, is well known, and a number of studies concerning individual air pollutants have appeared in the international literature. [1][2][3] The level of particulate matter (PM) has been of concern because several studies confirm that these particles may induce severe effects on public health. PM 10 (particles with aerodynamic diameter smaller than or equal to 10 µm), because of its size, may be inhaled and penetrate into the lungs, causing inflammatory reactions in the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Robeson and Steyn [12] predicted daily maximum ozone concentrations using three different statistical methods. Kartal and Ozer [6], using multiple regression analysis, determined and parameterized sulfur dioxide and smoke as a function of meteorological parameters which were wind speed and direction, percentage of relative humidity, air temperature, rainfall, amount of cloud cover, and the average global solar radiation in Kayseri, Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that SO 2 concentrations were strongly related to colder temperature, higher relative humidity and lower wind speed. For prediction of SO 2 and smoke concentrations, multiple regression equations including meteorological parameters and previous day's pollutant concentrations have been used (Kartal and Özer 1998). In another study presented by Turalıoğlu et al (2005), the relationship between daily average total suspended particulate and sulphur dioxide concentrations with meteorological factors for 1995-2002 winter seasons was statistically analyzed using the stepwise multiple linear regression analysis for Erzurum City.…”
Section: Introductionmentioning
confidence: 99%